Preconditioned HSS-Like Iterative Method for Saddle Point Problems (Journal of Computational Mathematics, 2018)
A new HSS-like iterative method is first proposed based on HSS-like splitting of non-Hermitian (1,1) block for solving saddle point problems. The convergence analysis for the new method is given. Meanwhile, we consider the solution of saddle point systems by preconditioned Krylov subspace method and discuss some spectral properties of the preconditioned saddle point matrices. Numerical experiments are given to validate the performances of the preconditioners.